Peresepsi Generasi Z Terhadap Tax Compliance - Juan Triasa Himawan, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study has a purpose, namely to prove the influence of tax knowledge, tax awareness, and tax attitude on tax compliance studies in Generazion Z. This study uses primary data. This study took the sample using the Non-Probability Sampling method with the Accidental approach. This study was conducted on people who have ages of 17-25 years and this study was conducted at four universities in the West Jakarta area. The total sample used in this study were 150 respondents. Research data were processed using SPSS Statistics version 20. The result of this study indicate that the influence of Tax Knowledge, Tax Awareness, and Tax Attitudes have a significant positive effect on Tax Compliance